E3-ubiquitin ligases and recent progress in osteoimmunology - Asano, Yosuke; Matsumoto, Yoshinori; Wada, Jun; Rottapel, Robert (Frontiers in Immunology, 2023)
Ubiquitin-mediated proteasomal degradation is a post-transcriptional protein modification that is comprised of various components including the 76-amino acid protein ubiquitin (Ub), Ub-activating enzyme (E1), Ub-conjugating enzyme (E2), ubiquitin ligase (E3), deubiquitinating enzyme (DUB) and proteasome. We and others have recently provided genetic evidence showing that E3-ubiquitin ligases are associated with bone metabolism, the immune system and inflammation through ubiquitylation and subsequent degradation of their substrates. Dysregulation of the E3-ubiquitin ligase RNF146-mediated degradation of the adaptor protein 3BP2 (SH3 domain-binding protein 2) causes cherubism, an autosomal dominant disorder associated with severe inflammatory craniofacial dysmorphia syndrome in children. In this review, on the basis of our discoveries in cherubism, we summarize new insights into the roles of E3-ubiquitin ligases in the development of human disorders caused by an abnormal osteoimmune system by highlighting recent genetic evidence obtained in both human and animal model studies.